Analisis Komparatif Model Pembelajaran Anak Usia Dini, Implikasi Pendekatan Instruksional Terhadap Keaktifan Kognitif dan Dinamika Sosial siswa - Maria Matilda Mao Ghari; Klementina Ye Meo; Hildegardis Jesika Beka; Fransiska Karolina Titu; Karolina Kugu; Maria Rosalinda Dhone; Maria Wulu; Hendrika Doa (Jurnal Pembelajaran dan Pendidikan Dasar, 2026)
This study aims to comparatively analyze two learning models in early childhood education (Class A and Class B) at the PLP 1 partner school and their impact on students' cognitive engagement and social dynamics. Employing a qualitative methodology based on the interactive analysis model of Miles, Huberman, and Saldaña, data were gathered through real-time observation of student activities, interviews with school authorities, and physical documentation. The findings indicate that both classes exhibit strong homogeneity in internalized character habituation (religiosity and self-regulation) and a humanistic evaluation policy free from homework (PR). However, a sharp instructional disparity emerged during core activities: Class A implemented a strictly teacher-centered model utilizing mechanical-imitative individual worksheets, resulting in low verbal participation and egocentric inquiry. Conversely, Class B adopted a collaborative student-centered approach using digital audio-visual media and manipulative family trees, which successfully boosted verbal participation to, fostered substantive inquiry, and facilitated active peer-to-peer interactive communication. This study concludes that a teacher's creativity in designing instructional scenarios and selecting multi-sensory media serves as the primary determinant in optimizing the cognitive and social potential of early childhood.